A Single Meal Containing Phytosterols Does Not Affect the Uptake or Tissue Distribution of Cholesterol in Zebrafish (Danio rerio) - van Spankeren, Michel; Sibinga, Nathaniel; Reinshol, Øyvind; Torstensen, Bente E.; Sæle, Øystein; Liland, Nina S. (Frontiers in Marine Science, 2019)
Increased plant oil inclusion in aquaculture feeds has led to higher dietary phytosterol concentrations and speculation about whether this affects the metabolism and health of the fish. The mechanisms of cholesterol absorption and how phytosterols may affect this is unknown in fish. Zebrafish (Danio rerio) were used to study the effects of phytosterols on the uptake and organ distribution of dietary cholesterol in fish. One meal of diets containing a constant addition of cholesterol (cold and [4-14C] cholesterol) and varying types and concentrations of phytosterols were fed to fish in individual compartments. The fish were not previously conditioned on the experimental diets. Activity of 14C was then measured in water and fish tissues to quantify the tissue distribution and excretion of cholesterol. There were no effects of the moderate dietary concentrations of phytosterols on the excretion or tissue distribution of dietary cholesterol 24 hours after the meal.